Sex and age differences in the early identification and treatment of alcohol use: a population-based study of patients with alcoholic cirrhosis - Otete, Harmony E.; Orton, Elizabeth; West, Joe; Fleming, Kate M. (Wiley, 2015)
Aim: To estimate sex differences in health-care utilization among harmful/hazardous drinkers in the period before alcoholic cirrhosis diagnosis, and estimate sex differences in the extent to which alcohol use and brief alcohol interventions were documented for these individuals compared with a control cohort.